A Methodology for Checking the Validity of an Existing Contour Map Using RTK-GPS and GIS (University of Khartoum Engineering Journal, 2022)
This paper presents a methodology for checking the validity of the height information of an existing contour map using RTK-GPS measurements and GIS analysis. In particular, 3D profiles were measured in the field by RTK-GPS. The same 3D profiles were extracted from a scanned and geo-referenced contour map using GIS. The height information from the two data sets of 3D profiles were compared in the absolute and relative sense. Thiscomparison reveals two aspects about the two data sets. First, the two data sets from the RTK-GPS measurementsand the existing maps are very similar in terms of shape, which suggest that both of them they capture the same underlying trend of the topography. Second, the maximum relative RMSE is  0.939 m in the first 3D profile that goes from the west to the east. The relative RMSE is a very important measure since it does not depend on the changes that may happened to the vertical datum (benchmark). These two findings leave us with two options. First, to accept the existing contour map; and this acceptance should be judged in light of the overall requirements and the design criteria of the project. For example, a global compensation can be made to accommodate the maximum variation in the topographic surface for an irrigation project. This compensation does not give any information about the local variation of the topography that may impact, for instance, a pivot irrigation design. Second, to redo the survey work. Indeed, both options are associated with obvious and hidden risks that may not be trivial during thedesign stage of the project. The first option can be accepted on the basis of a global compensation parameters that will be obtained from the comparison tests. And the second option will come with an instantaneous financial burden.